Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/gme.0000000000000714
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive history and risk of type 2 diabetes mellitus in postmenopausal women: findings from the Women's Health Initiative

Abstract: Objective To understand the association between women’s reproductive history and their risk of developing type 2 diabetes. We hypothesized that characteristics signifying lower cumulative endogenous estrogen exposure would be associated with increased risk. Methods Prospective cohort analysis of 124,379 postmenopausal women aged 50–79 from the Women’s Health Initiative. We determined age of menarche and final menstrual period, and history of irregular menses from questionnaires at baseline, and calculated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 40 publications
6
61
0
Order By: Relevance
“…Consistent with previous studies showing that late menopause can increase the diabetes risk, the present findings also showed that the age at natural menopause affected type 2 diabetes risk even after adjustment for age, BMI and other potential confounders, though the cut‐off points for menopausal age differed from the previous studies. Another two studies involving menopausal age ≥53 years, which was in line with our cut‐off point for later age at menopause in the present study, showed that the association was not statistically significant after multivariable adjustment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies showing that late menopause can increase the diabetes risk, the present findings also showed that the age at natural menopause affected type 2 diabetes risk even after adjustment for age, BMI and other potential confounders, though the cut‐off points for menopausal age differed from the previous studies. Another two studies involving menopausal age ≥53 years, which was in line with our cut‐off point for later age at menopause in the present study, showed that the association was not statistically significant after multivariable adjustment.…”
Section: Discussionsupporting
confidence: 91%
“…Both the European Prospective Investigation into Cancer and Nutrition (EPIC)-InterAct study in Europe 11 and Dongfeng-Tongji cohort study in China 12 have found that early menopause is associated with a greater risk of type 2 diabetes. Several other studies from the USA and China [13][14][15] reported that women with late menopause had an increased diabetes risk. Meanwhile, three studies from Italy, Japan and China found no effects of age at menopause on diabetes risk [16][17][18] .…”
Section: Introductionmentioning
confidence: 95%
“…One of the mechanisms that has been proposed to explain the association between early age at menarche and obesity is that earlier‐onset menarche might result in longer exposure to estrogen25 and adrenal steroids26, which tend to maintain adiposity. Furthermore, an overlap between single‐nucleotide polymorphisms implicated in the timing of puberty and in determining BMI in adulthood has been reported25. These single‐nucleotide polymorphisms include TCF , which was shown to be a risk factor for obesity and type 2 diabetes27, and LIN28B , which is associated with insulin sensitivity and oxidative stress‐related β‐cell apoptosis28.…”
Section: Discussionmentioning
confidence: 99%
“…The association between age at menarche and BMI was observed in both the <65 years and ≥65 years age groups. One of the mechanisms that has been proposed to explain the association between early age at menarche and obesity is that earlier-onset menarche might result in longer exposure to estrogen 25 and adrenal steroids 26 , which tend to maintain adiposity. Furthermore, an overlap between single-nucleotide polymorphisms implicated in the timing of puberty and in determining BMI in adulthood has been reported 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation